XRD, FTIR, 1H NMR, 13C NMR and UV Spectroscopic and Computational Studies of [3-(Hydroxyimino)butan - Kurnaz, P.; Ataol, C.Y.; Bati, H.; Büyuk̈güngör, O. (Taylor and Francis Inc. 325 Chestnut St, Suite 800 Philadelphia PA 19106, 2016)
[3-(hydroxyimino)butan-2-ylidene]furan-2′-carbohydrazide (1) has been synthesized and characterized by IR, 1H NMR, 13C NMR, UV/vis and X-ray diffraction. In addition to the experimental studies, the optimized structure, vibrational parameters, chemical shifts, thermodynamic properties, ionization energy, electron affinity, electronegativity, global chemical hardness and chemical softness of the molecule have been investigated by using DFT with B3LYP/6.311G(d, p) and PBEPBE/6.311G(d, p) basis sets. HOMO and LUMO energies were calculated by TD-DFT approach in two different solvents. The experimental results of the compound have been compared with theoretical results and it is found to show good agreement with calculated values. © 2016 Taylor & Francis Group, LLC.
Keywords: DFT; Energy Gap; Furan; Hydrazone; Oxime; Single Crystal